How many farmers in 2030 and how many will adopt climate resilient innovations? - Campbell, Bruce M.; Thornton, Philip K. (2014)
Despite an increasingly urbanized world, the number of smallholder farmers will continue growing fast, from 550 million farms today to roughly 750 million by 2030. In the past 15 years, the adoption of agricultural innovations among smallholder farmers was low, commonly ranging between 0 and 15%. Climate change, land degradation, steady urbanization, population growth and other global changes means smallholder agriculture has to rapidly evolve, has to adopt climate-resilient technologies on a large scale, and make the most of social and economic innovations. We can learn from and replicate the successful examples of scaling up of innovations such as mobile technologies and services, so that many smallholder farmers become climate resilient by 2030. ￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼